Health executives’ perceptions on marketing in health services: an empirical study in 9 hospitals of Attica - Malliarou, Maria; Roka, Basiliki; Zyga, Sofia; Kalokairinou, Athena; Sarafis, Pavlos (My University, 2009)
Introduction: The international financial crisis in combination with the aging population and the appropriation of funds of health services impose the management of hospital services as a necessity for the surviving of hospitals. Aim: To examine the perceptions of upper administrative hospital executives (Nursing, Medicine and Administrative services) in the wider region of Attica, on marketing, communication, and public relations in health. Materials and method: The research tool was a questionnaire that was titled “Attitudes and perceptions of health executives on marketing in health”. Section I, included 8 questions (questions 1-8) of which 3 collected information on the sex, the age and the level of education of those questioned. Section II, consisted 21 closed questions searching about the attitudes and perceptions of the people in the sample about marketing as activity in the area of health. Population study: Four hundred and fifty (450) higher health executives from the three basic fields of service in health institutions (medical, nursing, administration) constituted the total sample in the research. Results Most executives (n=216, percentage 48%) had favorable perceptions on the application of marketing in health services, quite a few executives (n=193, percentage 42,9%) had mediocre perceptions whereas a comparatively small number of these(n=41, percentage 9,1%) recorded a negative opinion. The women and older executives appeared to have a more positive stance compared to men (p=0,021) and younger executives (p=0,000). Nurses supported more intensely than doctors that the students of nursing had to have knowledge in marketing so that they are more equipped for their career. Nursing more than medical and administration personnel agreed with the perception that supports that marketing will decrease the dominance of the medical profession in the field of health. Conclusions: People in the survey even though they had some reservations they formed a favorable attitude towards marketing and its application in the field of health An extremely high percentage of the participants in the research agreed that marketing is an activity that needs to definitely be applied by health professionals. Also the majority of the people in the sample agreed that marketing will play a major role in the future in the accomplishment of the health organization’s goals.
Keywords: Attitude; Perception; Marketing; Strategy; Health services